Post-treatment Lyme Disease as a Model for Persistent Symptoms in Lyme Disease - Rebman, Alison W.; Aucott, John N. (Frontiers in Medicine, 2020)
It has long been observed in clinical practice that a subset of patients with Lyme disease report a constellation of symptoms such as fatigue, cognitive difficulties, and musculoskeletal pain, which may last for a significant period of time. These symptoms, which can range from mild to severe, have been reported throughout the literature in both prospective and population-based studies in Lyme disease endemic regions. The etiology of these symptoms is unknown, however several illness-causing mechanisms have been hypothesized, including microbial persistence, host immune dysregulation through inflammatory or secondary autoimmune pathways, or altered neural networks, as in central sensitization. Evaluation and characterization of persistent symptoms in Lyme disease is complicated by potential independent, repeat exposures to B. burgdorferi, as well as the potential for co-morbid diseases with overlapping symptom profiles. Antibody testing for B. burgdorferi is an insensitive measure after treatment, and no other FDA-approved tests currently exist. As such, diagnosis presents a complex challenge for physicians, while the lived experience for patients is one marked by uncertainty and often illness invalidation. Currently, there are no FDA-approved pharmaceutical therapies, and the safety and efficacy of off-label and/or complementary therapies have not been well studied and are not agreed-upon within the medical community. Post-treatment Lyme disease represents a narrow, defined, mechanistically-neutral subset of this larger, more heterogeneous group of patients, and is a useful definition in research settings as an initial subgroup of study. The aim of this paper is to review the current literature on the diagnosis, etiology, risk factors, and treatment of patients with persistent symptoms in the context of Lyme disease. The meaning and relevance of existing patient subgroups will be discussed, as will future research priorities, including the need to develop illness biomarkers, elucidate the biologic mechanisms of disease, and drive improvements in therapeutic options.